Flood Forecasting via Time Lag Forward Network; Kelantan, Malaysia - Jajarmizadeh M.; Mohd Sidek L.; Basri H.B.; Jaffar A.S. (Institute of Physics Publishing, 2023)
Errors; Flood control; Floods; Forecasting; Heuristic methods; Hyperbolic functions; Mean square error; Water levels; Critical issues; Flood forecasting; Flood periods; Hidden layers; Input and outputs; Optimum configurations; Root mean square errors; Water level forecasting; Weather forecasting; baseline conditions; catchment; data acquisition; dynamic property; error analysis; flood forecasting; hazard assessment; hydrological hazard; hydrological modeling; network analysis; numerical method; spatiotemporal analysis; water level; Kelantan; Malaysia; West Malaysia